2005-2009 : espacio líquido = liquid space - Ito, Toyo ([S.l.] : El Croquis, 2009)
Bringing together recent works and projects undertaken between 2005 and 2009, this collection emphasises Toyo Ito s consistent ability to create engaging designs for a diverse range of predominantly public facilities. Among the 15 projects featured in this issue are designs for the Fukuoka Island City Central Park Grin Grin, the Meiso no Mori Municipal Funeral Hall, Tama Art University Library, the White O project, the New Deichman Main Library, Oslo and the Market Street Tower, Singapore. Introduced by an interview between the architect and Sou Fujimoto and followed by and exploratory essay from Mohsen Mostafavi, all works are accompanied by full-page colour photographs and images, along with plans, elevations, Ito s delicate models and explanatory sketches.